Unravelling of cellulolytic fungal consortium from humus soil for efficient lignocellulosic waste degradation - H.K. Narendra Kumar; N. Chandra Mohana; Jayarama Reddy; M.R. Abhilash; S. Satish (The Microbe)
Cellulose is a complex polysaccharide composed of β 1, 4 glycosidic linkages and these linkages are broken down by a complex enzyme system called cellulase. Cellulase is an enzyme complex associated with β 1, 4 endoglucanase, β 1, 4 exoglucanase, and β glucosidase. The fungal strains were isolated from decomposed humus soil and screened for the best cellulolytic activity. Thirty-two isolates were screened among these; three were selected based on their morphological characters and hydrolytic capacity, viz, Cladosporium oxysporum N5, Aspergillus sigurros N6, and Cladosporium cladosporioides N12. Among these fungi, Cladosporium oxysporum N5 shows potential hydrolytic activity and was selected for optimization studies and evaluation of their cellulolytic capability. Cellulolytic strain Cladosporium oxysporum N5 produced maximum amount of cellulase enzyme at 5 days of incubation at 30 ℃ and pH 7, viz, β 1, 4 endoglucanase (167.83± U/ml), β 1, 4 exoglucanase (29.04± U/ml), and β glucosidase (34.07± U/ml). SEM coupled Energy dispersive X-ray and FTIR spectroscopy methods revealed the cellulose degradation efficiency of fungal cellulase by microscopic, elemental percentage, and functional group, respectively. An affordable and eco-friendly fungal-based cellulase that will boost industrially important commodity production such as food, beverages, pharmaceuticals, fertilisers, and biofuels.